Chronic breathlessness associated with poorer physical and mental health-related quality of life (SF-12) across all adult age groups. Issue 12 (29th March 2017) - Currow, D C; Dal Grande, E; Ferreira, D; Johnson, M J; McCaffrey, N; Ekström, M
Abstract : Little is known about the impact of chronic breathlessness (modified Medical Research Council (mMRC) score ≥2 for most days, at least three of the last six months) on health-related quality of life (Short Form-12 (SF-12)). 3005 adults from randomly selected households were interviewed face-to-face in South Australia. mMRC ≥2 community prevalence was 2.9%. Adjusted analyses showed clinically meaningful and statistically significant decrements of physical and mental components of SF-12 (mean SF-12 summary scores in physical (−13.0 (−16.0 to −10.2)) and mental (−10.7 (−13.7 to −7.8)) components compared with people with mMRC=0) as chronic breathlessness severity increased, across five age groupings.